Maternal Mortality in 19th- and Early 20th-century Italy. (5th February 2019) - Manfredini, Matteo; Breschi, Marco; Fornasin, Alessio; Mazzoni, Stanislao; De lasio, Sergio; Coppa, Alfredo
Summary: Although dramatically reduced in Western and developed countries, maternal mortality is still today one of the most relevant social and health scourges in developing countries. This is the reason why high levels of maternal mortality are always interpreted as a sign of low living standards, ignorance, poverty and woman discrimination. Maternal mortality represents, therefore, a very peculiar characteristic of demographic systems of ancien regime. Despite this important role in demographic systems, no systematic study has been addressed to investigate the impact of maternal mortality in historical Italy. The aim of this article is to shed some light on such a phenomenon by investigating its trend over time and the determinants in some Italian populations between the 18th and the early 20th centuries. The analysis will make use of civil and parish registers linked together by means of nominative techniques, and it will be, therefore, carried out at the micro level.